TINDAK TUTUR EKSPRESIF PADA EPISODE “BERANI BONGKAR DUGAAN DALANG TAMBANG ILEGAL” PODCAST CURHAT BANG DENNY SUMARGO - Linda Yustati, Emilia; Susilawati, Lis; Zahrotul Lutfiyah, Luly (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines how individuals express themselves through the disclosure of previously suppressed emotions in response to specific situations. The research was conducted on the Curhat Bang Denny Sumargo podcast channel, which featured Serly Tjoanda, the Governor of North Maluku, in an episode titled "Dare to Reveal! Suspected Mastermind of Illegal Mining." In the episode, Serly Tjoanda reveals various events related to alleged illegal mining after a long silence since her husband's death. This research is important for understanding an individual's psychological state in facing certain situations through John Searle's pragmatics, with a focus on expressive speech acts. This study aims to analyze the forms, functions, and types of expressive speech acts dominant in the podcast episode. The research data consists of podcast conversation transcripts, while secondary data were obtained from books, journals, scientific articles, and previous research related to speech acts. The results show seven forms of expressive speech acts, with a total of 20 data points: expressions of gratitude (2), apologies (2), happiness (2), praise (3), complaints (6), congratulations (2), and expressions of sadness (3).